State-Led Extractivism and Environmental Degradation in the Arctic: A Political Ecology Analysis - Nurhaliza, Siti; Hakiem, Fadhlan Nur (Center for Integrative International Studies Laboratory, Faculty of Political and Social Sciences, UIN Sunan Ampel Surabaya, 2026)
This paper analyzes how state-led resource competition exacerbates environmental degradation in the Arctic through a political ecology framework. The Arctic has transformed from a peripheral frontier into a geopolitical contestation arena driven by climate change and natural resource abundance. Using qualitative research methods and secondary source analysis covering 2010-2024, this study reveals how Arctic states' extractivism: including Russia, the United States, Canada, Norway, Denmark/Greenland, Nordic states, and China results in environmental consequences through climate change acceleration, marine ecosystem disruption, permafrost degradation, and black carbon pollution. Findings demonstrate that environmental degradation is systematically shaped by power relations prioritizing state interests and corporate profits over Indigenous sovereignty and ecological sustainability, with the paradox of